2021
DOI: 10.1101/2021.08.18.21262207
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of SARS-CoV-2 exposure in Malawian blood donors: a retrospective seroprevalence analysis between January 2020 and February 2021

Abstract: BackgroundAs at end of July 2021, the COVID-19 pandemic has been less severe in sub-Saharan Africa than elsewhere. In Malawi, there have been two subsequent epidemic waves. We therefore aimed to describe the dynamics of SARS-CoV-2 exposure in Malawi.MethodsWe measured the seroprevalence of anti-SARS-CoV-2 antibodies among randomly selected blood donor sera in Malawi from January 2020 to February 2021. In a subset, we also assesed in vitro neutralisation against the original variant (D614G WT) and the Beta vari… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…The copyright holder for this this version posted December 21, 2021. ; https://doi.org/10.1101/2021.12. 19.21268028 doi: medRxiv preprint the Delta wave suggested high levels of exposure to SARS-CoV-2 (40-60%) in South Africa 11,12 , Malawi 13 , and Zimbabwe 14 , and modelled estimates suggested seroprevalence of 70-80% across South Africa by October 2021 15 . Accordingly, the weeks following the third wave in South Africa, between 10 October and 15 November 2021, were marked by a period of lower-level transmission as indicated by a low incidence of reported COVID-19 cases (100-200 new cases per day) and low (<2%) test positivity rates (Fig.…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
“…The copyright holder for this this version posted December 21, 2021. ; https://doi.org/10.1101/2021.12. 19.21268028 doi: medRxiv preprint the Delta wave suggested high levels of exposure to SARS-CoV-2 (40-60%) in South Africa 11,12 , Malawi 13 , and Zimbabwe 14 , and modelled estimates suggested seroprevalence of 70-80% across South Africa by October 2021 15 . Accordingly, the weeks following the third wave in South Africa, between 10 October and 15 November 2021, were marked by a period of lower-level transmission as indicated by a low incidence of reported COVID-19 cases (100-200 new cases per day) and low (<2%) test positivity rates (Fig.…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
“…For example, early in the pandemic, the national lockdown in Nepal was associated with an increase in the institutional stillbirth rate and neonatal mortality, and a decrease in the quality of care (10). Malawi had registered 62,088 confirmed COVID-19 cases, 2,307 COVID-19 related deaths and 58,846 recoveries as of evidence of prior infection in February,2021, which is now reported to be as high as 80% in the city of Blantyre (southern region) (12). The pandemic has challenged the country's healthcare system, resulting in a disruption in the delivery of quality healthcare (13).…”
Section: Introductionmentioning
confidence: 99%
“…Malawi had registered 62,088 confirmed COVID-19 cases, 2,307 COVID-19 related deaths and 58,846 recoveries as of 10 th December 2021 (11). These absolute numbers of reported cases may also reflect limited testing capacity and uptake, as sero-surveillance has demonstrated that 51.1% of the population had serological evidence of prior infection in February,2021, which is now reported to be as high as 80% in the city of Blantyre (southern region) (12). The pandemic has challenged the country's healthcare system, resulting in a disruption in the delivery of quality healthcare (13).…”
Section: Introductionmentioning
confidence: 99%